2021
DOI: 10.3920/wmj2020.2592
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable biocholine as a hepatoprotectant in laying hens fed with diet contaminated with aflatoxin B1

Abstract: The aim of the study was to determine whether the addition of vegetable biocholine (VB) in laying hens feed minimises the effects of daily intake of aflatoxin B1 (AFB1). We allocated Hy-line Brown line laying hens into four groups with four replications/group and four birds/repetition. The treatments were as follows: Afla0Bio0: basal feed without aflatoxin and VB (natural contamination: 0.026 mg AFB1/kg), Afla0Bio800, basal feed supplementation of 800 mg VB/kg (natural contamination: 0.024 mg AFB1/kg); Afla2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…This reduced score in the HU is presumed to be due to the effects of AFs on egg formation and interference in the normal course of fat mobilization from the liver to the ovary ( Manafi, 2018 ). A lower yolk percentage and a higher proportion of albumen have been reported in laying hens as a result of AFB1 consumption ( Dazuk et al, 2021 ) which are not concurrent with the current experiment in which no significant differences were observed in yolk percentages and the higher percentages of albumen were observed in PC, NC, and MTB. This discrepancy might be due to the dosage of AFB1 (2,510 vs. 500 ppb) and temporal exposure to AFB1 (42 d vs. 12 wk).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This reduced score in the HU is presumed to be due to the effects of AFs on egg formation and interference in the normal course of fat mobilization from the liver to the ovary ( Manafi, 2018 ). A lower yolk percentage and a higher proportion of albumen have been reported in laying hens as a result of AFB1 consumption ( Dazuk et al, 2021 ) which are not concurrent with the current experiment in which no significant differences were observed in yolk percentages and the higher percentages of albumen were observed in PC, NC, and MTB. This discrepancy might be due to the dosage of AFB1 (2,510 vs. 500 ppb) and temporal exposure to AFB1 (42 d vs. 12 wk).…”
Section: Discussioncontrasting
confidence: 88%
“…This may lead to a decline in defense system to combat lipid peroxidation ( Bagherzadeh Kasmani et al, 2018 ). Augmenting lipoperoxidation and diminishing antioxidant capacity was also demonstrated in a study with laying hens in which birds were exposed to AFB1 for 42 d ( Dazuk et al, 2021 ). Therefore, a better function of liver through depressing MDA level by MF, MTA and MTB would seem to be the conclusion drawn from the current experiment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A study showed the efficacy of vegetable biocholine to improve the health of laying hens and the quality of eggs of the laying hens feed with a diet contaminated with AFB 1 (Dazuk et al, 2021). The use of Saccharomyces cerevisiae as probiotic in pig diets was effective to reduce the toxic effects of AFB 1 in intestines.…”
Section: Control Strategies To Reduce the Impact Of Mycotoxicosismentioning
confidence: 99%
“…Vegetable biocholine (VB) in fish diet improved health and performance [12]; when these fish were challenged with aflatoxin B1, biocholine had a hepatoprotective effect [12]. A similar effect was observed in laying hens exposed to aflatoxin B1 [13]. Based on this information, we aimed to determine whether adding VB to pigs' diet would minimize the adverse effects caused by daily aflatoxin intake, focusing on performance and health.…”
Section: Introductionmentioning
confidence: 99%